Entrepreneurship and Nineteenth Century Urban Growth: A Case Study of Orillia, Ontario, 1867-1898 - Noble, E. (Urban History Review / Revue d'histoire urbaine, 1980)
This article examines the role local decision-makers played in the development of Orillia. This small Ontario community exhibited as high a degree of boosterism as that found in much larger centres, and the economic growth of the town was primarily the result of growth strategies pursued by Orillia's entrepreneurial decision-makers. Although this group implemented a variety of successful growth strategies, this study concentrates on two of the most important. First, the businessmen supported a progressive railway policy which brought two competing lines to the community. This action enlarged the town's hinterland and enabled local businessmen to utilize a diverse pattern of buying and selling. Second, the entrepreneurs used the municipal corporation to finance the construction of North America's first municipally owned hydro-electric power system. This development enabled the town to successfully make the transition from a declining commercial centre to a small manufacturing town.